2004
DOI: 10.1080/00288233.2004.9513573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rhizobia from caucasian clover(Trifolium ambiguum)on nodulation and nitrogen fixation of white clover(Trifolium repens)

Abstract: Three glasshouse trials investigated N 2 fixation in white clover following inoculation with rhizobia from caucasian clover. We grew white clover in agar, vermiculite/perlite and soils low in available-N and with no detectable rhizobia. Media were subsequently treated with inoculum containing rhizobia effective on either (i) caucasian clover, (ii) white clover, or (iii) mixtures of the two. The percentage of ineffective nodules on white clover increased as the proportion of rhizobia from caucasian clover in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…The presence of 50% or 99% caucasian clover rhizobia in the soil had no significant effect (P>0.05) on white clover forage DM (Figure 4A), %N in the forage or calculated symbiotic N 2 fixation (Figure 4B) in either year. This result conflicts with the glasshouse results of Pryor et al (2004) who found that the presence of >92% of caucasian clover rhizobia in the population significantly reduced N 2 fixation in white clover. The lack of effect in the field trial can be explained by the small percentage of nodules formed on white clover by caucasian clover rhizobia.…”
Section: Forage Yield and N-uptakecontrasting
confidence: 97%
See 3 more Smart Citations
“…The presence of 50% or 99% caucasian clover rhizobia in the soil had no significant effect (P>0.05) on white clover forage DM (Figure 4A), %N in the forage or calculated symbiotic N 2 fixation (Figure 4B) in either year. This result conflicts with the glasshouse results of Pryor et al (2004) who found that the presence of >92% of caucasian clover rhizobia in the population significantly reduced N 2 fixation in white clover. The lack of effect in the field trial can be explained by the small percentage of nodules formed on white clover by caucasian clover rhizobia.…”
Section: Forage Yield and N-uptakecontrasting
confidence: 97%
“…Elliot et al (1998) drew attention to the possibility that the use of caucasian clover, and the associated build up of it's rhizobia in the soil, could lead to a reduction of symbiotic N 2 fixation by white clover. This is supported by results from glasshouse trials (Pryor et al 2004) where N 2 fixation in white clover was significantly reduced when ineffective caucasian clover rhizobia made up a high proportion (>92%) of rhizobia in the growth medium. These glasshouse results suggested that the use of the present strains of rhizobia for caucasian clover inoculants, and the possible build up of ineffective rhizobia in soil, may over time reduce N 2 fixation and hence productivity of white clover based pastures.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…This effect is of potential agronomic importance in New Zealand, where pastoral agriculture is largely based on WC/ryegrass pastures. Widespread use of CC will likely lead to the build-up of significant populations of CC rhizobia in soils with the potential to adversely affect WC growth (Elliot et al, 1998;Pryor et al, 2004).…”
Section: Introductionmentioning
confidence: 99%